THE POETICS OF SAVA HOLOVANIVSKYI’S ROMAN “TOPOLYA NA TOMU BEREZI”AND ITS RENDERING IN THE GERMAN TRANSLATION - Tkachivska, M. R.; Vintoniak, I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article discusses the comparison of the German translation with the original of Sava Holovanivskyi’s novel “Topolya na tomu berezi”. The rendering of epithets which convey the emotional charge of the book most effectively and phraseological unit swereanalyzed. Examples of inaccurate translations, omission of words, phrases and sentences are demonstrated. The ways of rendering are illustrated with examples from the original and its translation.